Advisability on the shift from standard front crawl swimming technique to the "kayaking" and "loping" variants - Zaton, K.; Szczepan, S.; Kazimirow, R.; Rejman, M. (Human Movement, 2012)
The aim of this study was to analyze selected kinematics parameters of standard front crawl swimming technique and its variants, the "kayaking" and "loping", in order to estimate the differences that can determine swimming effectiveness and efficiency Methods. Eighteen swimmers, divided equally into three groups, took part in the research. The first group was composed of individuals who favored the standard technique, the second group used the "kayaking" variant and the third one swam in the "loping" variant. All swimmers were instructed to swim the 50 m freestyle with their technique of choice at maximum velocity. Analysis of kinematic parameters (time, average swimming velocity), swimming cycle parameters (stroke length, stroke rate), and the swimming efficiency coefficient (stroke index) was calculated using SIMI`s 2D Reality Motion Systems software. Results. The Kruskal-Wallis test and Mann-Whitney U test found statistically significant differences in the studied parameters between the standard technique (S) and the "kayaking" (K) and "loping" (L) variants in the time to swim 25 m ( S = 15.472 s, K = 13.540 s, L = 14.108 s), and between (S) and (K) in the 15 m swim time ( St = 9.598 s, Kt = 8.593 s) and average swimming velocity ( Sv = 1.562 m/s, Kv = 1.757 m/s). Conclusions. Analysis of the differences in the kinematic parameters that define front crawl swimming technique finds justification in the need to modify the standard technique of the propulsive movement used in swimming towards those that employ the "kayaking" and "loping" variants as they are more effective in affecting swimming velocity.